Structural relaxation of ferroelectric phase in hard sodium lithium niobate solid solutions studied by solid-state NMR - Millena Logrado; Changhao Zhao; Hergen Breitzke; Jürgen Rödel; Gerd Buntkowsky (Scientific Reports)
Abstract Hard sodium lithium niobate (LNN) solid solutions offer a promising environmentally benign alternative to lead-based ferroelectric materials for electronic devices. A major challenge in their practical application is that their ferroelectric phase relaxes over a timescale ranging from weeks to years to an orthorhombic phase, limiting their long-term performance. In order to understand the structural changes in the relaxation process, high mechanical quality factor Li x Na1−x NbO3 solid-solutions were deliberately stored under ambient conditions for 24 months, without any specialized hermetic protection, to assess their stability over time. We utilized 1D and 2D 23Na solid-state Nuclear Magnetic Resonance (ssNMR) to investigate short-range structural changes in the 24-months-old aged and unaged Li x Na1−x NbO3 solid-solutions. NMR results reveal a system with phase-changes as a function of aging time and temperature. The samples exhibit a multiphase structure compromised of crystalline R and Q orthorhombic domains, along with two types of amorphous regions. A significant amount of ferroelectric phase persists in the ceramics after 24 months of exposure to ambient conditions. A structural model based on short-range order of sodium was suggested and agrees well with the lattice parameter of the freshly prepared samples.